2014
DOI: 10.1371/journal.pone.0107006
|View full text |Cite
|
Sign up to set email alerts
|

A Cell-Based High-Throughput Screen for Novel Chemical Inducers of Fetal Hemoglobin for Treatment of Hemoglobinopathies

Abstract: Decades of research have established that the most effective treatment for sickle cell disease (SCD) is increased fetal hemoglobin (HbF). Identification of a drug specific for inducing γ-globin expression in pediatric and adult patients, with minimal off-target effects, continues to be an elusive goal. One hurdle has been an assay amenable to a high-throughput screen (HTS) of chemicals that displays a robust γ-globin off-on switch to identify potential lead compounds. Assay systems developed in our labs to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…[Decreasing the concentration of 2,3-diphosphoglycerate inhibits polymerization by two mechanisms-increasing oxygen affinity and increasing solubility of HbS (25).] Highthroughput screens have been developed for the induction of HbF (42)(43)(44)(45)(46). The only high-throughput screen for antipolymerization compounds up until now tests for increasing oxygen affinity on isolated hemoglobin solutions, but it does not address the question of cell permeability (47).…”
Section: Discussionmentioning
confidence: 99%
“…[Decreasing the concentration of 2,3-diphosphoglycerate inhibits polymerization by two mechanisms-increasing oxygen affinity and increasing solubility of HbS (25).] Highthroughput screens have been developed for the induction of HbF (42)(43)(44)(45)(46). The only high-throughput screen for antipolymerization compounds up until now tests for increasing oxygen affinity on isolated hemoglobin solutions, but it does not address the question of cell permeability (47).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultured in HyClone Iscove's modified Dulbecco's medium (SH30005.02, Thermo Scientific) supplemented with 10% heat-inactivated FBS, 1ϫ penicillin/streptomycin, and the CID, 5 M CL-COB-II-293 (synthesized by the University of Kansas Centers of Biomedical Research Excellence Center for Cancer Experimental Therapeutics Core C Synthesis Lab; commonly called AP20187). The cells were passaged at 2 ϫ 10 5 cells/ml every 3 days in the presence of CL-COB-II-293 (55). WT ␤-YAC BMCs were treated with 10 M TMG for 4 days with fresh TMG and culture medium supplied daily.…”
Section: Cell Culturementioning
confidence: 99%
“…Hydroxyurea (HU), the single FDA-approved therapeutic has good activity in young patients and beneficial effects in approximately 50% of adults [5,7-10]. Additional non-cytotoxic HbF inducers, which could be used long-term, would be beneficial for treatment of patients with β-hemoglobinopathies [5, 63,67]. Clinical trials have shown significant HbF elevation, reduced anemia, and fewer hospital days in patients treated with arginine butyrate or decitabine, given parenterally [12,14].…”
Section: Discussionmentioning
confidence: 99%